MUC487 : Composition II / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course exposes students to the various terms, principles, organization, development, procedures, models and dimensions of composition. Students will learn how to present their scores using correct musical symbols and layout and prepare parts for performance.